Mapping The Scientific Landscape of Follow the Money Approach in Fraud Detection: Bibliometric Analysis Using Watase Uake - Syahrudin, Muhammad (Maksi, 2025)
This study aims to map the scientific landscape of the "Follow the Money" approach in fraud detection and forensic auditing through a systematic literature review and bibliometric analysis using the Watase Uake software. As financial crimes become increasingly complex in the digital era, the "Follow the Money" method serves as a critical tool for tracing illicit financial flows and uncovering fraudulent schemes. However, despite its practical application, academic literature related to this approach remains fragmented across various disciplines. By analyzing 10 selected articles from Scopus-indexed journals (Q1–Q4) between 2015 and 2025, this research identifies trends in keyword usage, author and journal impact, publication years, and thematic focuses. The findings reveal that while interest in this topic has grown, particularly in relation to anti-money laundering and governance, there is still a lack of methodological standardization and integration with digital audit tools. Moreover, the study highlights key research gaps, including limited empirical data, underdeveloped cross-jurisdictional frameworks, and insufficient attention to digital fraud and e-commerce contexts. Ultimately, this research contributes to advancing theoretical discourse and provides practical guidance for developing data-driven, transparent, and accountable forensic audit strategies in both public and private sectors.